2016
DOI: 10.5935/0034-7280.20160088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between phenol red thread test and the Schirmer’s test in the diagnosis of dry eyes syndrome

Abstract: Investigar a concordância entre o teste fenol vermelho e o teste de Schirmer para quantificação lacrimal junto a um questionário para detectar sintomas de olho seco. Métodos: No total, 49 pacientes participaram do estudo. Cada participante teve um olho examinado pelos dois testes. Os sintomas de olho seco foram avaliados através de 5 perguntas. Os dados foram coletados e depois analisados pelo método de estatísticas Kappa para avaliar a concordância entre os testes. Resultados: A sintomatologia foi positiva em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…In the IG, male participants were the most significantly affected, and trauma was the most frequent etiology (60%) for anophthalmia, in agreement with the results of Modugno et al [ 21 ], who reported that most of the 8018 anophthalmic participants evaluated between 1927 and 2011 were male and that 63% of the participants had a traumatic etiology of anophthalmia [ 22 ]. Regarding clinical history and symptoms, most participants complained of a feeling of having sand in the eyes, secretions in the eyelashes, and a tearing sensation.…”
Section: Discussionsupporting
confidence: 87%
“…In the IG, male participants were the most significantly affected, and trauma was the most frequent etiology (60%) for anophthalmia, in agreement with the results of Modugno et al [ 21 ], who reported that most of the 8018 anophthalmic participants evaluated between 1927 and 2011 were male and that 63% of the participants had a traumatic etiology of anophthalmia [ 22 ]. Regarding clinical history and symptoms, most participants complained of a feeling of having sand in the eyes, secretions in the eyelashes, and a tearing sensation.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the correction between the scores from different tests to detect dry eye is often poor [ 30 ]. The volume or production of tears can be assessed using the Schirmer or phenol red thread (PRT) tests [ 19 ]. The tear film stability can be measured using the tear breakup time (TBUT) test [ 31 ], and the concentration of electrolytes in the tear film can be assessed using the osmolarity test [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the tear film is complex; therefore, no single method can be used to detect all symptoms of dry eye [ 10 ]. Measurements of tear volume, production, evaporation, stability, and osmolarity are the most common methods for the detection of dry eye, along with the use of patient questionnaires [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of discomfort associated with dry eye can be detected using a questionnaire such as the ocular surface disease index (OSDI) [ 23 ]. The most common techniques for detecting dry eye and assessing the tear film include Schirmer [ 24 ], phenol red thread (PRT) [ 24 ], tear meniscus height (TMH) [ 25 ], noninvasive tear breakup time (NITBUT) [ 25 ], osmolarity [ 26 ], tear evaporation rate (TER) [ 27 ], and tear ferning (TF) [ 28 ] tests.…”
Section: Introductionmentioning
confidence: 99%